2020
DOI: 10.1186/s12891-019-2971-8
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous neoplasms of long bones: analysis of the surveillance, epidemiology, and end results database from 1973 to 2015

Abstract: Background: Malignant fibrous neoplasms (MFN) of long bones are rare lesions. Moreover, the prognostic determinants of MFN of long bones have not been reported. This study aimed to present epidemiological data and analyse the prognostic factors for survival in patients with MFN. Materials and methods: The Surveillance, Epidemiology, and End Results (SEER) programme database was used to screen patients with malignant fibrous neoplasms (MFN) of long bones from 1973 to 2015, with attention to fibrosarcoma, fibrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Through univariate and multivariate analyses, we determined that age, race, tumor grade, and historic stage were closely associated with prognosis ( Table 2 ). We did not find that chemotherapy was an independent prognostic factor for OS, and the results were consistent with a recent study [ 26 ]. Based on this, a nomogram was created to facilitate clinical work ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through univariate and multivariate analyses, we determined that age, race, tumor grade, and historic stage were closely associated with prognosis ( Table 2 ). We did not find that chemotherapy was an independent prognostic factor for OS, and the results were consistent with a recent study [ 26 ]. Based on this, a nomogram was created to facilitate clinical work ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Adult fibrosarcoma occurs most frequently in the trunk and limbs, followed by the head and neck, consistent with our results [ 25 ]. Tumor size of malignant fibrous neoplasms (MFN) of long bones >10 cm is a poor prognostic factor for OS and cancer-specific survival [ 26 ]. A report on primary intracranial fibrosarcoma suggested that large tumor volume (≥5 cm) and high Ki-67 index (≥30%) were independent risk factors for OS [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 94 studies that shared a major study question with at least one other study, 35% (33 of 94) reported discordant key findings concerning 10 study questions [1, 6, 8, 11‐13, 18, 23, 26, 29, 36, 39‐41, 44, 49, 53, 59, 63, 67, 68, 72, 79, 83, 93, 95, 98‐100, 106, 109‐111] (Table 2), 29% (27 of 94) reported mixed key findings concerning six study questions [3, 7, 15, 19, 22, 25, 27, 28, 30, 35‐37, 43, 45, 47, 50, 56, 75, 76, 82, 88‐91, 103, 104, 107] (Table 3), and 44% (41 of 94) reported concordant key findings concerning 12 study questions [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112] (Table 4). Of the 299 studies in total, 20% (59 of 299) reported discordant or mixed findings [1, 3, 6‐8, 11‐13, 15, 18, 19, 22, 23, 25‐30, 35‐37, 39‐41, 43‐45, 47, 49, 50, 53, 56, 59, 63, 67, 68, 72, 75, 76, 79, 82, 83, 88‐91, 93, 95, 98‐100, 103, 104, 106, 107, 109‐111] and 14% (41 of 299) reported concordant findings [2, 4, 5, 14, 16‐18, 20, 24, 31, 33, 38, 42, 46, 48, 52, 57, 58, 61, 71, 74, 75, 77, 78, 81, 84‐87, 91, 92, 96, 97, 101, 102, 105, 106, 108, 110‐112]. Examples of topics with discordant or mixed findings include the effect of radiation on survival in several sarcoma types and the influence of race on treatment and survival.…”
Section: Resultsmentioning
confidence: 99%